Review of Altmetric Index Articles of Iranian Medical Publications Indexed in PubMed Information Database in Scientific Social Media - Abbas Doulani; Layla Rasouli Ghotorlar; Amir Ghaebi (نشریه مطالعات دانش‌پژوهی, 2024)
Purpose: The aim of this study is to explore the articles included in the Altmetric index of Iranian medical journals that are listed in the PubMed database within scientific social networks.Methodology: This applied research utilized a survey methodology and a scientometric approach based on altmetric indicators. The statistical population for this study comprised all medical articles from 2018 available in the PubMed medical database. Data collection was facilitated through the use of the bookmarklet tool, which is accessible for free on the Altmetrics Institute website.Findings: The results revealed that 23% of the articles mentioned at least once on social networks received an altmetric score. The average citation count for articles with an altmetric score was 2.91. The altmetric average for all articles was 0.6 compared to the average citation count of 1.6, indicating that articles received roughly a single citation for every altmetric score. Among social networks, Twitter was the most popular with 1036 articles (21%), followed closely by Mendeley with 935 articles (19%).Conclusion: The coverage of altmetrics for articles in Iranian medical journals listed in the PubMed database was found to be satisfactory. The study also highlighted a significant and positive correlation between the number of citations received and the altmetric score, suggesting that articles with higher citation counts were also more frequently discussed on social networks.Value: This article provides insights into the altmetrics of medical science articles indexed in a reputable medical database, with the measured indicators relevant for use in various scientific social networks.